Translation and psychometric evaluation of the Diabetes Education Questionnaire (DATE-Q) from English to Marathi – assessing reliability, validity, and cross-cultural equivalence - Kulkarni, Sharvari J.; Lima de Melo Ghisi, Gabriela; Jaiswal, Varoon C.; Pawar, Pournima; Kharatmal, Deepali R.; Kangude, Mithali M. (Rzeszów University Press, 2025)
Introduction and aim. The DiAbeTes Education Questionnaire (DATE-Q) is a self-administered tool created to evaluate disease-related knowledge and knowledge of five core components of rehabilitation: exercise, diet, psychological well-being, self-management and complications. The aim was to translate and adapt the DATE-Q into Marathi language and to evaluate the validity and reliability among diabetes and prediabetic patients. Material and methods. The study was carried out following standard stepwise Beaton and COSMIN guidelines to complete the translation and psychometric validation of the questionnaire. The pre-final version was evaluated in 30 individuals with diabetes or prediabetes. Test-retest reliability and internal consistency were assessed among 200 individuals with type 2 diabetes using Cronbach’s alpha and intraclass correlation coefficients respectively. Results. The original and translated versions did not conceptually differ from each other. DATE-Q has ten elements that were culturally adjusted. Based on suggestions from the expert group and the results of the pilot tests, cross-cultural modifications were made. The value of 0.935 for Cronbach’s alpha shows a very high level of internal consistency. For single and average measures, the intraclass correlation coefficient is 0.985 and 0.993 resp. which indicates an excellent level of reliability. Conclusion. The DiAbeTes Education Questionnaire is a reliable and valid tool for evaluating knowledge among Marathi-speaking patients.
All subjects gave their informed consent for inclusion before they participated in the study. The study was conducted in accordance with the Declaration of Helsinki, and approved by the Ethics Committee of the MIT’s MAEER Physiotherapy College, Talegaon Dabhade (approval number: EC/NEW/INST/2019/377/183).
Keywords: cross cultural evaluation; diabetes mellitus; health education; psychometric evaluation; reliability; validity